Cytotoxicity, inflammation, biomineralization, and immunoexpression of IL-1 beta and TNF-alpha promoted by a new bioceramic cement - Cosme-Silva, Leopoldo; Santos, Amanda Ferreira dos; Lopes, Camila Soares; Dal Fabbro, Renan [UNESP]; Benetti, Francine; Gomes-Filho, Joao Eduardo [UNESP]; Azevedo Queiroz, India Olinta de [UNESP]; Ervolino, Edilson [UNESP]; Viola, Naiana Viana (Univ Sao Paulo Fac Odontologia Bauru, 2020)
Aim: To evaluate the cytotoxicity, biocompatibility and mineralization capacity of BIO-C PULPO, and MTA. Methodology: L929 fibroblasts were cultured and MTT assay was used to determine the material cytotoxicity on 6, 24, and 48 h. A total of 30 male rats (Wistar) aged between 4 and 6 months, weighing between 250 and 300 g were used. Polyethylene tubes containing BIO-C PULPO, MTA, and empty tubes were implanted into dorsal connective tissue. After the experimental periods (7, 15, 30, 60, and 90 days) the tubes were histologically analyzed using hematoxylin-eosin (H&E), immunolabeling of IL-1 beta and TNF-alpha, and von Kossa staining, or without staining for polarized light analysis. The average number of inflammatory cells was quantified; the mineralization assessment was determined by the area marked in pmt and semiquantitative immunolabeling analyses of IL-1 beta and TNF-alpha were performed. Then, data underwent statistical analysis with a 5% significance level. Results: It was observed that BIO-C PULPO and MTA presented cytocompatibility at 6, 24, and 48 similar or higher than control for all evaluated period. On periods 7 and 15 days, BIO-C PULPO was the material with the highest number of inflammatory cells (p<0.05). On periods 30, 60, and 90 days, BIO-C PULPO and MTA presented similar inflammatory reactions (p>0.05). No statistical differences were found between Control, BIO-C PULPO, and MTA for immunolabeling of IL-1 beta and TNF-alpha in the different periods of analysis (p<0.05). Positive von Kossa staining and birefringent structures under polarized light were observed in all analyzed periods in contact with both materials, but larger mineralization area was found with BIO-C PULPO on day 90 (p<0.05). Conclusion: BIO-C PULPO was biocompatible and induced mineralization similar to MTA.
Keywords: Biocompatibility; Biomaterials; Cytotoxicity; Pulpotomy; Dental Pulp